(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Nine sections from the "Limestones and marls with Rhaetavicula contorta" Auctt. (Norian-Rhaetian) of the Tuscan Nappe in eastern Liguria and northwestern Tuscany, have been examined for their stratigraphic and sedimentological characteristics. The results obtained have been integrated with data pertaining to the previously studied Pania di Corfino section. Two formations were identified and studied in detail: that of Pania di Corfino and that of La Spezia. Where present, the Pania di Corfino Formation accounts for the lower portion of the sections. It consists mainly of thick beds and massive layers of dolomites, dolomitic limestones and limestones. Thinly-bedded dark limestones appear less frequently, while layers rich in clay are rare. The top of the formation is surely of Rhaetian age, in some sections, as indicated by the presence of Triasina hantkeni Majzon; in the others, it is Norian-Rhaetian. The age of the bottom portion can be regarded as Norian-Rhaetian in all the sections; the presence of considerably thick deposits beneath the established Rhaetian layers in some sections, however, suggests an Early Rhaetian or even Late Norian age. The depositional environment of the Pania di Corfino Formation may be envisaged as an epicontinental carbonate platform with predominantly restricted water circulation on which fine carbonate sediments are deposited beneath the wave base; features suggesting a tidal flat are rare. The environment of deposition was, for brief periods only, that of a platform with open circulation in which the effects of wave-motion were prominent; features strictly relatable to a true platform edge have not been found.